Impacto de la Educación Formal y Migración en el Desempeño de las Empresas Familiares: Un Caso en Jerez, Zacatecas - Héctor Gabriel Villegas-Berumen; Humberto Morales Magallanes; César Landeros Soriano (Nova Scientia)
This research is the result of observing the performance phenomenon of family businesses (FBs) in relation to the formal education level of participating members of their administration, aiming to establish a relationship between both variables. This study was conducted through the design of a survey as a measurement instrument, with a reliability of α = 0.741, applied to a sample of n = 280 companies, using statistical hypothesis tests: 1) One-way ANOVA, 2) Student's t-test for a single sample, and 3) Hypothesis testing with two samples for verification. It was found that companies whose average educational level is high do not necessarily have better performance expectations in a Mexican urban area with low economic growth, due to the phenomenon of migration at an early age. It is important to emphasize that the data collected for the purpose of this research were obtained in the locality of Jerez, in the state of Zacatecas; therefore, its results can only be generalized to locations with similar social, economic, and demographic conditions.